PEMAHAMAN MASYARAKAT TERHADAP KEWAJIBAN ZAKAT DI KECAMATAN ILIR BARAT II KOTA PALEMBANG - Citra Pertiwi (Jurnal I-Philanthropy, 2021)
This journal examines the extent to which efforts must be made so that an understanding of zakat obligations builds awareness for zakat in Ilir Barat II sub-district, in this study a case study is carried out on the things that are the factors of opportunities and obstacles to the implementation of zakat with good, transparent, and accountable management. , examines the techniques and strategies that must be done to achieve good management. In the implementation of zakat, there is a gap that is very suitable for the Muslim community to carry out the pilgrimage, which is greater than with the implementation of other pillars of Islam, for example, zakat. This is influenced by internal and external factors of the Muslims themselves, including, the knowledge and understanding of the not yet comprehensive tithe and the lack of application of zakat ritual values ​​in social life. In this study, the type of "Quality" data is used, which is data obtained by studying and trying to explore phenomena in society as an objective source of data in the field about people's understanding of zakat obligations in Ilir Barat II District, Palembang City in improving understanding of the third pillar of Islam. for the Muslim community in Ilir Barat II sub-district. The results of the study indicate that the perception of the Islamic community in Ilir Barat II District in general does not understand what the meaning and purpose of zakat is, they only assume that zakat obligations are only limited to orders but the benefits of people who pay tithe can purify our assets so that they are clean from all kinds of selfishness, miserliness and miserliness. . where the current understanding of society is only limited to fiqhi and rituals of worship, zakat is considered a means of perfecting worship in the holy month of Ramadan as an obligation which, if fulfilled, is already released from its obligations. In fact, zakat is a sunnatullah capable of releasing people from the problems of poverty. To make the implementation of zakat efficient in improving the quality and performance of zakat management services through the implementation of economic development programs for community members, especially people who are classified as poor. It is necessary to immediately draw up strategic plans, vision-missions, and objectives of the UPZ (Zakat Collection Unit) at the RT and Kelurahan levels in Ilir Barat II sub-district, so that the implementation process (both collection and distribution) can be measurable, efficient, and on target. It is necessary to empower zakat funds to create productive businesses in accordance with the level of understanding and skills possessed by the community and the level of community needs in Ilir Barat II sub-district. It is necessary to cooperate with all sectors and stakeholders in the community to carry out the zakat empowerment movement with various ideas for economic development and productive efforts in order to create a prosperous society.